Notes on the Vertebrates of northern Pará, Brazil: a forgotten part of the Guianan Region, II. Avifauna - Aleixo, Alexandre; Poletto, Fabíola; Lima, Maria de Fátima Cunha; Castro, Marcelo; Portes, Eduardo; Miranda, Leonardo de Sousa (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2011)
We carried out seven two-week long avifaunal inventories in five newly-established conservation units spanning the entire ‘Calha Norte’ area, a portion of the Guiana Shield in the northern part of the state of Pará, Brazil, between January 2008 and January 2009. Prior to our study, most of this part of Amazonia was regarded as virtually unsampled from an ornithological perspective. Here, we present an annotated check-list with 446 species of birds recorded during the surveys, including 62 species for which our records represented significant range extensions, and hence are discussed in detail. The number of species recorded at each site varied between 203 and 302, and was positively correlated with the local availability of steep altitudinal and vegetational (forest/savanna and seasonally-flooded/upland forest) gradients. The number of unique species recorded at each site varied between 2 and 27, and reflected an interesting biogeographic pattern in which the Trombetas river appears to separate distinct upland and white-sand forest bird faunas on the Guiana Shield, a pattern also verified for the herpetofauna. Our results also showed that savannas represent a very important component of the local biota, with enclaves harboring a typical bird fauna also distributed in similar habitats in nearby southern Guyana, Suriname, and the state of Amapá in Brazil. Altogether, the five conservation units surveyed harbour 74 bird species of special interest for conservation (threatened, endemic, rare, range-restricted, and hunted species) and therefore play a key role in the preservation of all main subsets of the heterogeneous bird fauna of the Guiana Shield.